The Application of Modified SBA-15 as a Chemosensor - Ziarani, Ghodsi M.; Khademi, Mahdieh; Mohajer, Fatemeh; Badiei, Alireza (Current Nanomaterials, 2022)
The Santa Barbara Amorphous (SBA-15), with a large surface area covered with abundant Si-OH active groups on the walls of its pores, can be modified with various organic compounds to build organic-inorganic hybrid materials, which can be used as a catalyst in organic reactions, drug delivery systems, nano sorbent due to its high capacity for removing heavy metals in waste water and as chemosensors for ions. Tunable and straight channels of SBA-15 facilitate the entrance and diffusion of ions through the channels. This paper presents a review of the past five years of literature covering the application of SBA-15 as an ions chemosensor in the liquid and gaseous media.
Keywords: nano sorbent